I am not able to get an answer for this problem. 8÷4[6-2(-8+3*2^3)] can you help?

## 8÷4[6-2(-8+3*2^3)] I cannot get this problem solved and simplified.

# 2 Answers

I believe the solution provided by the above user is correct upto the 4th to the last line.

Use PEMDAS=> parentheses, exponential, multiplication, division, addition, subtraction (left to right)

After you have gotten the stuff within the brackets simplified upto [6-32] = [**-26**], the expression becomes,

8÷4[-26] (since we still have the bracket, we have to deal with it first)

= 8 ÷ (-104) (a÷b is same as a/b, eg. 4÷2 = 4/2 = 2)

= -1/13 (minus sign from -104 carries)

To simplify, we'll be using PEMDAS (order of operations)

P - Parentheses first

E - Exponents (ie Powers and Square Roots, etc.)

MD - Multiplication and Division (left-to-right)

AS - Addition and Subtraction (left-to-right)

8÷4[6-2(-8+3*2^3)] Inner Parentheses first

= 8÷4[6-2 (-8+3*8) ] Exponent within parentheses

= 8÷4[6-2 (-8+24) ] Mult within parentheses

= 8÷4[6-2 (16) ] add/subt within parentheses

= 8÷4 [6-2 (16)] Now the bracket

= 8÷4 [6-32] Mult within bracket

= 8÷4 [26] subt within bracket

= 8÷4 [-26] since were left with mult and division, we'll go from left to right

= 2 (-26) mult

= -52

## Comments

When completing the final simplification within the bracket [6-32], the result is a

negaitive26, not apositive26. Thus, the next simplification will be 8 ÷ 4 [-26]. The simplification for 8 ÷ 4 is 2 and 2 times -26 is -52. So the final answer isnegative52, notpositive52.Comment